(untitled) (Analytical Methods for Drug Development, 2025)
Author Mr. Wilberforce Kasangaki PG Scholar, Dept of Regulatory Affairs, Ramanbhai Patel College of Pharmacy, CHARUSAT, Changa, Gujarat, India Abstract Method validation establishes analytical procedure reliability through systematic performance evaluation. ICH Q2(R1) guidelines provide validation frameworks adaptable across development phases from early research through commercialization. Risk-based approaches align validation effort with method purpose and product criticality. Validation parameters include specificity testing against potential interferents, linearity across concentration ranges, accuracy through recovery studies, precision at repeatability and intermediate levels, detection and quantitation limit determination, and robustness evaluation through deliberate parameter variations. Statistical analysis applies outlier testing, equivalence assessment, measurement uncertainty calculation, and confidence interval determination to validation data, enabling science-based acceptance criteria. Method transfer between laboratories requires comparative testing protocols with predefined acceptance criteria and troubleshooting pathways for failed transfers. Documentation encompasses validation protocols, comprehensive reports, and lifecycle management plans including change control triggers and revalidation requirements. Keywords: Analytical method validation, Method Transfer Protocols, Validation Acceptance Criteria, Statistical Validation VIEW PDF